2020
DOI: 10.14715/cmb/2019.66.1.14
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability of E. histolytica strains based on the polymorphism of the SREHP gene using nested PCR-RFLP in Erbil, North Iraq

Abstract: E. histolytica is an intestinal parasite that causes asymptomatic infection mostly; however, it may also cause amoebic dysentery and liver abscess. Molecular identification is required in epidemiological studies due to the presence of morphologically identical nonpathogenic species. Therefore, this study was conducted to first evaluate the prevalence rate of E. histolytica among symptomatic individuals of Erbil city, and to investigate the genetic diversity of the parasite in a limited geographic area. Accordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…For examples, studying STR regions in tRNA genes of E. histolytica revealed interspecies variation that may related to the clinical outcome of the disease and may provide evidence for the geographic origin of the infection [67]. Moreover, studies documented the presence of high genetic diversity among E. histolytica strains using PCR-RFLP analysis on SREHP gene and addressed the association of the strains with the clinical presentation of the disease [8,44,68]. The investigations based on chitinase gene sequence repeat suggested the existence of strains of E. histolytica that could be non-pathogenic, invasive for the intestinal mucosa or invasive for liver tissue [46,69,70].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For examples, studying STR regions in tRNA genes of E. histolytica revealed interspecies variation that may related to the clinical outcome of the disease and may provide evidence for the geographic origin of the infection [67]. Moreover, studies documented the presence of high genetic diversity among E. histolytica strains using PCR-RFLP analysis on SREHP gene and addressed the association of the strains with the clinical presentation of the disease [8,44,68]. The investigations based on chitinase gene sequence repeat suggested the existence of strains of E. histolytica that could be non-pathogenic, invasive for the intestinal mucosa or invasive for liver tissue [46,69,70].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the presence of these genetic alterations could have either permitted the parasite to more readily evade host immune responses or be related to higher virulence, causing more severe clinical presentations [8].…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the nature of amoebic virulence is important, several studies have shown that the genetic factors do in uence the virulence of the infection. Among the many loci used to investigate the epidemiology of E. histolytica, Chitinase and SREHP are among the important markers used in molecular epidemiological studies [11].…”
Section: Introductionmentioning
confidence: 99%
“…Different types of genes associated with the outcome of amebic infection have been detected, Among the many loci used to investigate the outcome of E. histolytica infection, SREHP and chitinase are one of the important markers used in these studies [11]. These proteins have been shown to be potentially useful for determination of intra-species variation among E. histolytica and in investigating the molecular epidemiology of amebiasis.…”
Section: Introductionmentioning
confidence: 99%